ANALISIS KESALAHAN BERBAHASA PADA SURAT RESMI ORGANISASI KELUARGA BESAR MAHASISWA FKIP UNTIRTA TAHUN 2018 (ANALYSIS OF LANGUAGE ERRORS IN THE OFFICIAL LETTER OF THE STUDENT FAMILY ORGANIZATION FKIP UNTIRTA IN 2018) - Tisnasari, Sundawati (Kantor Bahasa Banten, 2020)
This scientific article examines language errors in the official letter of the 2018 KBM FKIP UNTIRTA organization on PUEBI (Indonesian Spelling General Guidelines) and official letter provisions. The process of collecting data is done by referring to the technique and the technique of recording the collected data is classified according to the topic of the study. The data analysis technique is descriptive qualitative. The conclusions of this study are First, there were errors of 77 errors with the distribution of errors using PUEBI (General Indonesian Spelling Guidelines) as many as 59 errors and TKSR (Provisions for Official Letter Structure) as many as 18 errors; Second, the type of PUEBI error that dominates, namely capital letter usage errors; The three organizations that made mistakes were dominated by LSIP UKM (Student Activity Unit of the Circleof Islamic Studies and Education). Keywords: language error analysis, PUEBI, official letter structure provisionsArtikel ilmiah ini mengkaji kesalahan berbahasa pada surat resmi organisasi KBM FKIP UNTIRTA tahun 2018 pada tinjauan PUEBI (Pedoman Umum Ejaan Bahasa Indonesia ) dan ketentuan surat resmi. Proses pengumpulan data di lakukan dengan teknik simak dan teknik catat data yang terkumpul diklasifikasikan berdasarkan topik kajian. Teknik analisis data bersifat deskriftif kualitatif. Simpulan dari penelitian ini adalah Pertama, terdapat kesalahan sebanyak 77 buah kesalahan dengan pembagian kesalahan penggunaan PUEBI (Pedoman Umum Ejaan Bahasa Indonesia) sebanyak 59 kesalahan dan TKSR (Ketentuan Struktur Surat Resmi) sebanyak 18 buah kesalahan; Kedua, Jenis kesalahan PUEBI yang mendominasi, yaitu kesalahan pemakaian huruf besar; Ketiga organisasi yang melakukan kesalahan didominasi oleh UKM LSIP (Unit Kegiatan Mahasiswa Lingkar Studi Islam dan Pendidikan).Â Kata Kunci:analisis kesalahan berbahasa, PUEBI, ketentuan struktur surat resmi